2022
DOI: 10.1139/facets-2021-0106
|View full text |Cite
|
Sign up to set email alerts
|

Undermining environmental assessment laws: post-assessment amendments for mines in British Columbia, Canada, and potential impacts on water resources

Abstract: In British Columbia (BC), Canada, there is increased attention on mines and their impacts on water resources. In BC, many proposed mines undergo provincial environmental assessment (EA), which predicts a mine’s risks and involves government oversight and public engagement. After approval, mines can apply for amendments that alter the project’s undertakings, including in ways that may harm water resources. We examined all amendment documents for mines undergoing provincial EA in BC from 2002 to 2020. Of the 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Collison et al ( 178 ) recently highlighted a regulatory loophole that may enable harm to freshwater systems from mining operations once the impact assessment process has concluded. Their systematic examination of approved and operating mines in BC found that 65% requested amendments after approval, with 98% of requests approved.…”
Section: The Science Of Mining Policymentioning
confidence: 99%
“…Collison et al ( 178 ) recently highlighted a regulatory loophole that may enable harm to freshwater systems from mining operations once the impact assessment process has concluded. Their systematic examination of approved and operating mines in BC found that 65% requested amendments after approval, with 98% of requests approved.…”
Section: The Science Of Mining Policymentioning
confidence: 99%
“…The environment also includes social, cultural, and (for humans) economic and political considerations, as well as the more usually understood features such as soil, climate, and food supply." 18 The Supreme Court of Chile had this to say on the environment: "[T]he environment, environmental heritage and preservation of nature, of which the Constitution speaks and which it secures and protects, is everything which naturally surrounds us and that permits the development of life, and it refers to the atmosphere as it does to the land and its waters, to the flora and fauna, all of which comprise nature, with its ecological systems of balance between organisms and the environment in which they live." 19 In the same vein, the New Zealand Environment Act of 1986 defines the environment as including:…”
Section: Understanding the Term Environmentmentioning
confidence: 99%
“…17 Dupuy and Viñuales, n15, 24 citing F. Ramade, 'Dictionaire Encyclopedique de l'ecologie et des Sciences de l'environnment' (Dunod 2002) 279. 18 Dupuy and Viñuales, n15, 24 citing Michael Allaby, 'Oxford Dictionary of Ecology' (3 rd edn, Oxford University Press 2005) 154. 19 Pedro Flores v Codelco, División Salvador (1988) Rol.…”
Section: Understanding the Term Environmentmentioning
confidence: 99%
See 1 more Smart Citation